Propuesta de una Ruta Agroturística en los barrios Loma Redonda y Santa bárbara del cantón olmedo provincia de Loja - Armijos Ochoa, Servio Hernani (2018)
Tourism has become one of the most important industries worldwide, especially in developing countries there are huge expectations for what this market can contribute to their economies. In recent years it has reached an unprecedented dimension becoming a complex phenomenon that, depending on how it is managed, can open horizons to culture or put it in danger. Agrotourism is a form of tourism in which rural culture is used economically to provide diverse options of distraction with nature, mainly with cultivated landscapes. The fundamental purpose of agricultural tourism is to create a new culture of healthy crops and, as a consequence, efficient, profitable and competitive crops. For the realization of the present research topic, a general objective was raised; Prepare an agrotourism route in the neighborhoods Loma Redonda and Santa Bárbara del Cantón Olmedo, province of Loja; and for its fulfillment there are three specific objectives: To carry out the tourist diagnosis to know the current situation of the Loma Redonda and Santa Bárbara neighborhoods of Olmedo Canton, province of Loja, the tourist diagnostic matrix of Carla Ricaurte Quijano was made; to determine the current tourist situation of the place; In the same way, the analytical method was used, which allowed a study of the attractions, their condition and the possible problems that exist. Also the direct observation, interviews, books, web pages, thesis works, information of the Municipal GAD of Olmedo, methodology and summary files to inventory tourist attractions of MINTUR, the same that allowed to perform an analysis of its type, hierarchy and sub kind. To fulfill the second objective: Propose an agrotourism route for the neighborhoods Loma Redonda and Santa Bárbara, the inductive and deductive methods were used, which helped in the elaboration of the proposal of promotion of the tourist product; where the design of the route of most important attractions was determined, taking strategic points of georeferencing (GPS), maps, itinerary and based on the MINTUR signaling manual, the pictograms and signals for the present agrotouristic route "Las Delicias del Coffee and Peanuts ". In the third objective: Socialization with those involved in the agrotourism route of the neighborhoods Loma Redonda and Santa Bárbara of the canton Olmedo, Province of Loja, the synthetic method was used for the development of the socialization workshop for example through the technique of MARPP the same one that is conformed by three phases: The first initial (Previous) invitation, agenda and presentations. The second: (Execution) development, presentation of the theme with the support of audiovisual material. Third: (Results) conclusions and suggestions where we will have as a result this Agrotourism Route "Las Delicias del Café y Maní" which will be a contribution for the development of the Canton. 5 Among the most important conclusions was that the neighborhoods where the agrotouristic route proposal was developed have a variety of tourist attractions and agrotourism activities, which have not been promoted for the knowledge of the different tourists, there is no tourism department in the GAD Municipal del Olmedo, limited tourist facilities, lack of tourist signage and limited interprovincial public transport. It is recommended that this research work be carried out for the tourist development of the Canton, to the authorities to carry out self-management of tourism projects, economic resources, public transport and training workshops related to tourism activity; those involved in the agrotourism route improve their infrastructure and customer service to boost the development and influx of tourists in the Canton.